Release mechanisms and applications of drug delivery systems for extended-release. (1st September 2020) - Wang, Shuying; Liu, Renhe; Fu, Yao; Kao, W. John
ABSTRACT: Introduction: Drug delivery systems with extended-release profiles are ideal in improving patient compliance with enhanced efficacy. To develop devices capable of a prolonged delivery kinetics, it is crucial to understand the various underlying mechanisms contributing to extended drug release and the impact thereof on modulating the long-term performance of such systems in a practical application environment. Areas covered: This review article intends to provide a comprehensive summary of release mechanisms in extended-release drug delivery systems, particularly polymer-based systems; however, other material types will also be mentioned. Selected current research in the delivery of small molecule drugs and macromolecules is highlighted. Emphasis is placed on the combined impact of different release mechanisms and drug properties on the long-term release kinetics in vitro and in vivo . Expert opinion: The development of drug delivery systems over an extended duration is promising but also challenging when considering the numerous interrelated delivery-related parameters. Achieving a well-controlled extended drug release requires advanced techniques to minimize burst release and lag phase, a better understanding of the dynamic interrelationship between drug properties and release profiles over time, and a thorough elucidation of the impact of multiple in vivo conditions to methodically evaluate the eventual clinical efficacy.